Memories of old Manila [videorecording] - Philippines. National Commission for Culture and the Arts. (Manila NCCA, 1993)
An exploration of five centuries of Manila, and into the lives of street kids, addicts, transvestites and student activists who cross paths with imaginary figures of mermaids, giants and Oliver who represents Philippine underground cinema.
Filipino dialogue, English subtitles.
VHS.
Keywords: Manila -- History; Activists -- Philippines -- Manila; Experimental films -- History and criticism. -- Philippines; Manila -- Social conditions; Street children -- Philippines -- Manila